Bakteri Ve Oksin Uygulamalarının Kuşburnu Bitkisinin Çelikle Çoğaltılması Üzerine Etkileri - Kınık, Elif Durmuş; Çelikel, Fisun Gürsel (My University, 2017)
Rosa canina L. çelikleri sonbahar mevsiminde Ondokuz Mayıs Üniversitesi Kurupelit Kampüsü florasından temin edilmiştir. Yarı odunsu çelikler, sisleme ve alttan ısıtma sistemi olan köklendirme masasına, 1:1 oranında torf ve perlit karışımına dikilmiştir. Çalışmada 10 farklı rizobakteri (bitki gelişimini düzenleyen) izolatı tek başına ve 1000 ppm oksin (Indole-3-butyric acid-IBA) ile birlikte uygulanmıştır. Çelikler 6 saat bakteri uygulamasından sonra, dikim öncesi 10 saniye IBA çözeltisinde bekletilmiştir. Köklenme oranı, kök yumağı eni, kök boyu ve ana kök sayısı saptanmıştır. En yüksek köklenme oranı Bacillus megaterium, Bacillus megaterium ve Pseudomonas flourescens uygulamalarında %30 olarak saptanmıştır. Kontrolde %10 oranında köklenme görülürken, IBA bazı bakterilerin etkisini değiştirmemiş (Bacillus subtilis, Agrobacterium rubi, Paenibacillus polymyxa), bazılarında hafif düşüşe yol açmış (Bacillus megaterium), buna karşın tek başına hiç köklenme sağlamayan 3 bakteri izolatı (Bacillus megaterium, Bacillus subtilis, Pseudomonas putida) %10 oranında köklenme göstermiştir. Bakteri uygulamaları genel olarak, köklenme oranı dışında köklenme kalitesini (kök yumağı eni, kök boyu ve ana kök sayısı) artırmıştır.

Rosa canina L. cuttings were obtained from the flora of Ondokuz Mayıs University campus of Kurupelit. Woody cuttings were placed into the medium of perlite and turf mixture with a ratio of 1:1 under mist propagation system with bottom heating system. Rosa canina cuttings were treated with 10 different plant growth promoting rhizobacteria (PGPR), alone or with the combination of 1000 ppm auxin (Indole-3-butyric acid-IBA), before planting into rooting medium. Cuttings were first kept in solution for 6 h and then treated with 1000 ppm IBA for 10 seconds. The rooting ratio, the diameter of rooting area, root length and the number of main roots were determined. According to the results, the highest rooting ratio was obtained from Bacillus megaterium (M-3), Bacillus megaterium (TV-60D) and Pseudomonas flourescens (TV-11D) bacteria treatments by 30% whereas rooting ratio was 10 % for control cuttings. IBA did not change the effects of some bacteria (Bacillus subtilis, Agrobacterium rubi, Paenibacillus polymyxa), slightly reduced the effects on some bacteria (Bacillus megaterium), whereas provided 10% rooting on some bacteria (Bacillus megaterium, Bacillus subtilis, Pseudomonas putida) which were not effective alone. In general, bacteria treatments improved the rooting quality (diameter of rooting area, root length and the number of primary roots) other than rooting ratio.
Effects of Plant Growth Promoting Bacteria and Auxin on Cutting Propagation of Rosa canina L.
Keywords: Ziraat Mühendisliği; Gıda Bilimi ve Teknolojisi